Fostering Integrity: Implementation Of Internal Control In The General Merchandise Businesses In The City Of San Fernando, La Union - Janille L. Miranda,; Gracelle D. Bautista,; Avegail C. Cariño,; April Joy A. Damisel,; Janila R. Estioco, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Implementing internal control in general merchandise businesses allows them to achieve long-term sustainability by safeguarding their assets, preventing fraudulent activities, and optimizing operational efficiency. The study was conducted to determine the extent of implementation of internal control, the extent of deterrence of fraud, and the relationship between the extent of implementation of internal control and the extent of deterrence of fraud. Data from 110 general merchandise businesses was gathered using a validated questionnaire and analyzed using frequency and mode and Spearman’s rho. Findings revealed that most respondents have a very high implementation of internal control while few do not; most have a very high deterrence of fraud while many do not. It also showed that a few of the indicators in the extent of implementation of internal control and the extent of fraud deterrence have a significant but weak relationship. In contrast, most do not have a significant relationship.